SYMBOLIC INTERACTIONISM OF THE MAIN CHARACTER IN THE “NOAH” MOVIE: A SOCIOLINGUISTIC ANALYSIS - Ria, Nurul Miftahurrahmah; Mustikawati, Yunitari; Sahril, Sahril (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This research is entitled " Symbolic Interactionism of the Main Character “Noah” in the Noah Movie: A Sociolinguistic Analysis." This study aims to analyze how the symbolic interactionism reflected of the main character “Noah” in the “Noah Movie by Darren Aronofsky (2014) by using George Harbert Mead’s theory (1937) the types of Symbolic Interactionism attaching symbols to object, actions, and interactions. The analysis method used refers to the sociolinguistic analysis by considering Blumer (1986) theory to explore the interpret meaning from their social interactions especially ‘Noah’ as the main character in the movie. Descriptive qualitative research is used in this study. Data obtained from the text of conversations between the main character and other characters that contain elements of symbolic interactionism. The results of this research show that there are 25 screenshots of the main character scenes in total as the data that has been collected from “Noah” movie. The findings provide deep insight into how the main character “Noah” reflects Symbolic Interactionism in various way such us personal appearance, verbal and nonverbal communication, self-concept, perceptions of others and role-taking. And from the 25 extracts obtained, the researcher also concludes that the use of symbolic interactionism on the main character focuses on object, person, and action, and especially how the final result is obtained and consists of presented meaning, language and thoughts from the symbolic interactionism of the main character. This research is expected to contribute to the understanding of literature and how the reflected of Symbolic Interactionism of the main character in the movie literary works.Keywords: Symbolic Interactionism, Noah, Movie, Sociolinguistic